Laser ultrasonic visualization technique using a fiber-optic Bragg grating ultrasonic sensor with an improved adhesion configuration. (January 2021) - Yu, Fengming; Saito, Osamu; Okabe, Yoji
In this research, we attempt to establish a reliable structural health monitoring technique for composite materials by combining phase-shifted fiber-optic Bragg grating sensing with the laser ultrasonic visualization technology. In the first part of this article, a novel cross-adhesion configuration is designed to resolve the directionality problem of the phase-shifted fiber-optic Bragg grating ultrasonic sensing. In the adhesion configuration, Lamb waves are guided by an orthogonally bonded optical fiber from the adhesion point to the phase-shifted fiber-optic Bragg grating sensor. The analysis of the ultrasonic measurement results reveals that the proposed adhesion method enables us to use one sensor to receive Lamb waves in all in-plane directions with similar magnitude because two wave components propagating along with the two orthogonal directions are guided to the phase-shifted fiber-optic Bragg grating sensor and exhibit a linear superposition in the sensor. This simplified configuration gives our method an advantage over the existing approaches, such as the rosette configuration in which three or more phase-shifted fiber-optic Bragg grating sensors are required to relieve the sensing directionality. The phase-shifted fiber-optic Bragg grating ultrasonic sensor with the proposed adhesion configuration is then applied to visualize the propagation of ultrasonic waves in aluminum plates and carbon fiber–reinforced plastic laminates. Those verification experiments also show us that the new adhesion configuration is effective at protecting the phase-shifted fiber-optic Bragg grating ultrasonic measurement from the sensing directionality. Meanwhile, the broad bandwidth of the phase-shifted fiber-optic Bragg grating sensor enables us to visualize the propagation behavior of various Lamb wave modes over a broad frequency range. Finally, we also validate that the ultrasonic visualization technique merged with the phase-shifted fiber-optic Bragg grating ultrasonic sensing can be used to identify the hidden damage in the carbon fiber–reinforced plastic composite.